Revolutionizing political participation: a modified UTAUT model for generation Z in the digital era - Amin, Muryanto; Ritonga, Alwi Dahlan; Situmorang, Tonny Pangihutan; Santoso, Anang Dwi (Frontiers in Political Science, 2025)
IntroductionThis study investigates social media–based political participation among Generation Z in North Sumatra, a multicultural region representing Indonesia’s sociocultural diversity. The research integrates a modified UTAUT model with connective action theory to explain how technological factors shape political engagement in digital environments.MethodsData were collected from 500 university students and analyzed using Structural Equation Modeling (SEM). The model assesses the effects of performance expectancy, effort expectancy, social influence, and facilitating conditions on behavioral intention and actual political participation, with political awareness tested as a moderating variable.ResultsThe findings show that behavioral intention significantly mediates the relationship between technological determinants and political participation. Political awareness strengthens or weakens these relationships, and higher levels of political awareness are associated with lower intention to use platforms such as Instagram, TikTok, Twitter, and Facebook for political activities. The results also reveal the emergence of third spaces or hybrid activism that blend online and offline participation.DiscussionThese results demonstrate that social media enables flexible and decentralized political engagement while highlighting the complex role of civic awareness in shaping digital political behavior. The integrated framework advances the literature on digital politics by explaining how personalized political expression, technology use, and civic awareness interact to influence democratic participation in multicultural contexts.